The H2S Corrosion Effect On The Stationary Turbine Blade - Thomas Agus Bayu Prasetyo; Hamdan akbar Notonegoro; Ova Kurniawan; Sunardi Sunardi (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2021)
The Geothermal fluids were disturbed by volcanic gas sulfide deposit reactions which form by reaction of metal(s) with H2S. this sulfate acid is one of the most corrosive compounds in the steam which lead the pitting, stress corrosion cracking and other corrosion mechanisms. An optical microscope, XRF dan X-ray diffraction is used to observe the sediment samples that came from stationary blades. The results show that it mainly consists of 89.7%wt iron sulfide (FeS) and 10.3%wt arsenic trisulfide (As2S3). This phase is toxic by inhalation and ingestion. Downstream steam pipeline treatment is required to reduce sulfide carried away into steam turbines such as scrubbing or washing steam. For this reason, special handling is needed for the toxic waste resulting from washing.